Etnomathematics: Exploration of Geblek Renteng Batik in Transformation Geometry - Fatkhurohman Fatkhurohman; Annis Deshinta Ayuningtyas; Muchamad Subali Noto; Sri Adi Widodo (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2021)
This research is purposed for exploring Ethnomatematics geblek renteng batik in Kulonprogo, and this type of research is a qualitative descriptive with an ethnography approach. The collected data is qualitative, as the resource is gained from the observation, interview, and documentation related to batik geblek renteng the research instrument is a private research. The technic of data collection is gained from deep interview and documentation, the aid that is used in this research is interview guidance and documentation. The validation data is done by doing qualitative descriptive analysis. The result of the research shows that the motifs on batik geblek renteng contain a mathematics concept. The identification results from geblek renteng batik as the triangle elements, parallelogram, translation, reflection, rotation, and dilatation. The math concept on batik geblek renteng in addition to the introduction of culture, it also to be expected for one of the application math learning based on the culture process.